Adaptive Channel Coding and Modulation Scheme Selection for Achieving High Throughput in Wireless Networks - Sharif, Atif; Potdar, Vidyasagar; Ahmad, R. (IEEE Computer Society, 2010)
Modern wireless communication demands reliable data communication at high throughput in severe channel conditions like narrowband interference, frequency selective fading due to multipath and attenuation of high frequencies. Traditional single carrier systems address this set of problems by the use of complex, computationally intensive equalization filters. The Orthogonal Frequency Division Multiplexing (OFDM) based system, as opposed to single-carrier systems, is considered to be the future of the wireless communication and is being used to achieve high data rate by overcoming severe channel conditions without the use of these complex filters.This paper discusses the problem of Adaptive Modulation scheme selection through an OFDM based system over parallel frequency selective fading channels. An adaptive coding scheme is proposed by using Generalized Concatenated Codes (GCC), which have simple structure and are designed in such a way that they are best suited for fading channels. GCC are based on binary cyclic codes. The criterion of the proposed research is to optimize the throughput of a wireless system. Depending on the quality of sub-channels an adaptive modulation selection scheme and code assigning method is proposed. The proposed research combats against channel impairments better than those used in conventional systems by exploiting individual sub-channel condition. Results show better performance in terms of higher throughput by minimizing the bit error rate.